Penyelesaian Ganti Kerugian Dalam Perkara Pidana Berdasarkan Penetapan Praperadilan: Studi Di Pengadilan Negeri Jakarta Selatan - Rahman Amin; Iren Manalu; Winda Apricilya Van Hemert; Muh Fikri Al Aziz (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2022)
The Indonesian state of law means that everything in the administration of government, including the law enforcement process, is carried out in accordance with applicable legal provisions and for acts of arrest, detention, prosecution and trial of a person who is not based on law, wrongfully against a person, or in the application of the law, that person is entitled to obtain compensation to provide justice. This research is a normative juridical law research, with a statutory approach, where legal material is obtained through literature study. The results of the study indicate that the settlement of compensation based on a pretrial determination cannot be carried out by the Ministry of Finance because there is no Minister of Finance Regulation as a provision for the implementation of compensation payments. The inhibiting factors for the settlement of compensation are the legal substance factor, namely the Decree of the Minister of Finance regarding compensation that is not relevant to the current situation but has not been changed, the factor of differences in perception about the party responsible for the settlement of compensation, and the unavailability of a budget specifically allocated for the settlement of compensation.